Pariwisata Kreatif Pada Argowisata Perkebunan Teh Gunung Manik Desa Karyamukti Kabupaten Cianjur - Raflyanto Athallah; Rehulina Apriyanti (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2023)
The tea plantation located in the Karyamukti Village location is a tea plantation owned by Perhutani West Java and used as HGU land by PT Sinar Sosro. Agricultural agrotourism is a form of tourism that offers agricultural activities as the main attraction, takes advantage of artificial natural beauty, and involves the surrounding community as the manager of the tourist area. In addition,